A Big Five facet analysis of a psychopath: The validity of the HDS mischievous scale of sub‐clinical psychopathy. Issue 2 (26th January 2016) - Furnham, Adrian; Crump, John
Abstract : Around 5, 700 British adults completed the NEO‐PI‐R, which measures the Big Five Personality factors at the Domain and the Facet level, as well as the Hogan Development Survey (HDS); measure of Anti‐Social Personality Disorder called Mischievous . Previous work in this field has used clinical measures of psychopathy and either student or patient samples. This sought to validate this measure by comparing NEO facet correlational results with other studies. The Mischievous score from the HDS was the criterion variable in the correlations and multiple regressions. Mischievous people were Disagreeable, Stable, Extraverts, lacking in Conscientiousness. Facet analysis showed them high on Excitement‐seeking but low of Straightforwardness, Anxiety and Deliberation. Limitations are of the study are discussed.